Aging parents’ caregiving and rehabilitating a brain-injured son: an autoethnography of a 10-year journey - Syed Hassan, Syed Tajuddin; Jamaludin, Husna (Electronic Physician, 2014)
This autoethnography withdraws from information accumulated through a 10-year period of daily-weekly-monthly descriptive observation-recording (triangulated- parents & house-helper) of caregiving and rehabilitating of our brain injured son (survivor/care-receiver). We present it as an interactive voice of verbal conversation, thoughts, insights, and interpretations. It is delivered as a series of articulation intra-pulsated with our interrogation of societal-cultural-religious perspectives, norms and biases, and aligns with the CAP (Creative Analytical Practices) method of Ellis. This autoethnography glows from the richness of information which encapsulates the challenges confronting us the aging parent caregivers, the gradual incremental mind mending achievement of our son, and the interactive verbalizations and thoughts, of the caregivers, care-receiver, and other persons. The overwhelming mental and physical pain and struggle of the survivor and the aging caregivers and their sense of celebratory-satisfaction with rehabilitation progress are highlighted. Interpretation and valuation of positive and negative responses of other persons provide a critical matrix to this autoethnography. We intend to inform other caregivers and relevant healthcare professionals through this autoethnography.